1989
DOI: 10.1007/bf00320228
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal gammopathy in chronic myeloproliferative disorders

Abstract: The incidence of monoclonal gammopathy in 61 patients with chronic myeloproliferative disorders (CMPD) was studied. The distribution of patients among the CMPD subgroups was: chronic myelocytic leukemia, 24 patients; myelofibrosis, 11; polycythemia vera, 15; essential thrombocythemia, 7; unclassified MPD, 4 patients. Monoclonal gammopathy was found in 5 patients (8.2%). Two of these patients (1 IgA/k and 1 IgM/k) had myelofibrosis and 3 (2 IgG/k and 1 IgG/lambda) polycythemia vera. The presence of monoclonal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In a prospective study conducted in 61 MPN patients (median age 62 y) in Greece from 1982 to 1987 by Economopoulos et al, 26 8.2% (n ¼ 5) of patients were found to have coexisting MGUS, which is higher than the prevalence reported in the general population at approximately 1% to 3%. 27,28 Of these 61 patients, 37 had a Philadelphia chromosome-negative MPN (15 PV; 7 ET; 11 MF; 4 unclassifiable); 24 patients had chronic myeloid leukemia (CML).…”
Section: Coexistence Of Mpn and Mgusmentioning
confidence: 82%
“…In a prospective study conducted in 61 MPN patients (median age 62 y) in Greece from 1982 to 1987 by Economopoulos et al, 26 8.2% (n ¼ 5) of patients were found to have coexisting MGUS, which is higher than the prevalence reported in the general population at approximately 1% to 3%. 27,28 Of these 61 patients, 37 had a Philadelphia chromosome-negative MPN (15 PV; 7 ET; 11 MF; 4 unclassifiable); 24 patients had chronic myeloid leukemia (CML).…”
Section: Coexistence Of Mpn and Mgusmentioning
confidence: 82%
“…MPN including PV have also been associated with monoclonal gammopathy 17–20 . Economopoulos et al 17 reported monoclonal gammopathy in 8.2% out of 61 patients with MPNs. Randi et al 18 and Javorniczky et al 20 reported these rates to be 3.1% and 9% of cases, respectively, identifying higher rates in such patients than those in age‐ and sex‐matched controls; however, these results were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In 3-14% of MPN patients, a monoclonal gammopathy can be identified [38][39][40][41] , probably coincidentally 39 though one study has reported its presence to be associate with an adverse MPN disease course. 41…”
Section: B I O C H E M I S T Rymentioning
confidence: 99%